Effectiveness of a Community-Based Intervention to Improve Nutrition in Young Children in Senegal : A Difference in Difference Analysis - Alderman, H. (2012)
There are few studies of community growth promotion as a means of addressing malnutrition that are based on longitudinal analysis of large-scale programmes with adequate controls to construct a counterfactual. The current study uses a difference in difference comparison of cohorts to assess the impact on the proportion of underweight children who lived in villages receiving services provided by the Senegal Nutrition Enhancement Project between 2004 and 2006. The project, designed to extend nutrition and growth promotion intervention into rural areas through non-governmental organisation service providers, significantly lowered the risk of a child having a weight more than 2 sd below international norms. The odds ratio of being underweight for children in programme villages after introduction of the intervention was 0.83 (95% CI 0.686, 1.000), after controlling for regional trends and village and household characteristics. Most measured aspects of health care and health seeking behaviour improved in the treatment relative to the control.